Mining high-viscosity consolidation material and preparation method thereof
By using the combination of specific components in the mineral consolidation materials, the high-definition and bridge bond structure of mineral high-adhesion consolidation materials are solved, and efficient construction and good durability are achieved.
Patent Information
- Application Number
- CN202510414408.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-03
AI Technical Summary
The existing inorganic consolidation materials have low strength after hardening, long curing time and large rebound rate, which affects construction efficiency.
The mineral high-adhesive consolidation material consisting of components A, components B and components C are used to fill the gaps of cement particles through fly ash and slag cement. The polyurethane emulsion and cellulose are used in combination to form a bridge bond structure to improve the density and strength of the material.
It significantly improves the compressive strength and adhesion of the consolidated material, shortens the settling time, and improves the durability and flame retardant effect of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mining reinforcement and sealing materials, in particular to a mining high-viscosity consolidation material and a preparation method thereof. Background Art
[0002] Mining consolidation materials are generated by a two-component substance mixed in a volume ratio of 1:1 under low temperature conditions. After the material is injected into the formation, it can quickly penetrate fine cracks, expand and solidify, and use its own excellent connection and bonding properties with rocks to connect broken rocks into a whole, increase the supporting force of the rock formation, ensure production safety, and be easy to use. Therefore, it is often used in mines to prevent weathering of mine surrounding rocks, rusting of metal supports, spontaneous combustion of coal seams, leakage of harmful gases, etc. It is also suitable for the closure of permanent large tunnels, bottom parking lots, tunnels, blocking of toxic and harmful gases, and can be sprayed onto the surface of rock masses and other areas.
[0003] At present, there are two commonly used consolidation materials: inorganic consolidation materials and organic consolidation materials. Among them, organic consolidation materials have a high reaction temperature and pose certain safety hazards, so inorganic consolidation materials are more commonly used. However, the strength of inorganic consolidation materials after hardening is low, the curing time is long, the rebound rate is large, and the manual construction is long, which affects the efficiency. Summary of the invention
[0004] In order to improve the strength of inorganic consolidation materials, the present invention provides a high-viscosity consolidation material for mining and a preparation method thereof.
[0005] The first aspect of the present invention is to provide a high-viscosity consolidation material for mining, which adopts the following technical solution: A high-bonding material for mining, comprising component A, component B and component C in a weight ratio of 1: (0.5-1): (0.5-1), wherein component A comprises the following raw materials in parts by weight: 35-45 parts of rapid-hardening sulphoaluminate cement, 20-30 parts of coal gangue powder, 15-20 parts of sulphoaluminate cement, 2-5 parts of expansion agent, 0.5-1.5 parts of water reducing agent, 5-10 parts of fly ash, 5-8 parts of slag cement, 0.2-0.8 parts of lithium carbonate and 1-3 parts of retarder; The B component includes the following raw materials in parts by weight: 60-70 parts of Portland cement, 5-12 parts of calcium carbonate, 10-15 parts of calcium oxide, and 1-3 parts of retarder; The C component comprises the following raw materials in parts by weight: 70-80 parts of polyurethane emulsion, 1-3 parts of cellulose, 9-22 parts of water, and 0.5-1 part of water reducing agent.
[0006] Preferably, the A component comprises the following raw materials in parts by weight: 40-45 parts of rapid hardening sulphoaluminate cement, 25-30 parts of coal gangue powder, 17-20 parts of sulphoaluminate cement, 3-4 parts of expansion agent, 1.0-1.5 parts of water reducer, 5-10 parts of fly ash, 5-8 parts of slag cement, 0.2-0.8 parts of lithium carbonate, and 1-3 parts of retarder; The B component includes the following raw materials in parts by weight: 65-70 parts of Portland cement, 6-9 parts of calcium carbonate, 12-15 parts of calcium oxide, and 1-3 parts of retarder; The C component comprises the following raw materials in parts by weight: 75-80 parts of polyurethane emulsion, 2-3 parts of cellulose, 9-22 parts of water, and 0.5-1 of water reducing agent.
[0007] By adopting the above technical scheme, after the component A in the present application is mixed with the component B and the component C, the fly ash and slag cement as ultrafine mineral powders can be effectively filled in the voids of the fast-hardening sulphoaluminate cement particles, and when the fast-hardening sulphoaluminate cement solidifies and hardens, the expansive agent will expand with the volume to generate prestress, fully fill the voids of the cement, and effectively improve the density of the consolidated material, thereby helping to improve the strength of the consolidated material; in addition, the addition of lithium carbonate in component A can not only react with the water in the consolidated material to generate lithium hydroxide, absorb and release the cement hydration heat, and reduce the shrinkage and cracking of the consolidated material caused by temperature changes, but also the lithium carbonate participates in the cement hydration reaction to form a dense protective film, which prevents acidic substances and salts from corroding the internal structure of the material and improves the durability of the consolidated material.
[0008] The addition of calcium carbonate and calcium oxide in component B has the effect of promoting cement hardening and improving the strength of the consolidated material.
[0009] The combined use of polyurethane emulsion and cellulose in component C can prevent the generation of cracks in the consolidation material during the drying and shrinkage process and improve the strength of the consolidation material. The reasons may be: the polyurethane emulsion plays a bridging and active role in the consolidation material, wherein the active groups in the polyurethane emulsion exchange with the free calcium ions, aluminum ions and iron ions in the cement hydration to form a special bridge bond, which undergoes physical and chemical adsorption around the cement particles to form a continuous phase with high uniformity, reduces the overall elastic modulus, improves the physical organization structure and internal stress state of the cement slurry, increases the deformation capacity of the consolidation material, and greatly reduces the possibility of generating micro cracks. Even if micro cracks are generated, the development of the cracks can be limited due to the bridging effect of the polyurethane emulsion; secondly, since the polyurethane emulsion contains a certain amount of surfactant, it can reduce water and disperse cement particles, thereby improving the workability of the cement slurry and reducing water consumption, thereby reducing harmful pores such as capillaries in the cement slurry and improving the compaction performance of the cement slurry.
[0010] Therefore, the synergistic effect of the raw materials in the present application can not only shorten the setting time of the consolidated material, but also improve the compressive strength and adhesion of the consolidated material, so that the initial setting time of the consolidated material is within 15 minutes, the final setting time is within 40 minutes, the 1-day compressive strength reaches more than 25 MPa, and the 3-day compressive strength is more than 28 MPa.
[0011] Preferably, the C component also includes 10-15 parts by weight of gypsum.
[0012] Preferably, the fly ash is Class I fly ash.
[0013] Preferably, the expansion agent is a plastic expansion agent, a UEA expansion agent, or a combination of both.
[0014] Preferably, the weight ratio of the plastic expansion agent to the UEA expansion agent is 1:1.
[0015] By adopting the above technical solution, when the expansion agent adopts a combination of a plastic expansion agent and a UEA expansion agent, not only the density of the consolidated material can be improved, but also shrinkage cracking can be prevented, thereby making the density of the consolidated material better and improving the strength of the consolidated material.
[0016] Preferably, the retarder consists of sodium gluconate, tartaric acid and citric acid in a weight ratio of 1:(0.5-1.2):1.
[0017] Preferably, the solid content of the polyurethane emulsion is 40-50%.
[0018] A second aspect of the present invention provides a method for preparing a high-viscosity consolidation material for mining, comprising the following steps: Mix and stir the raw materials in component A for 10-20 minutes to obtain component A; mix and stir the raw materials in component B for 10-20 minutes to obtain component B, mix and stir the raw materials in component C for 10-20 minutes to obtain component C, then stir and mix component A and half of component C for 10-20 minutes to obtain mixture one, stir and mix component B and the remaining half of component C for 10-20 minutes to obtain mixture two, and then stir and mix mixture one and mixture two for 10-20 minutes to obtain a high-viscosity consolidation material for mining.
[0019] By adopting the above technical solution, after the raw materials of component A, component B, and component C are mixed separately, component A is mixed with half of component C, component B is mixed with the remaining half of component C, and then the two are mixed. This can make the raw materials mixed more evenly, which helps to improve the bonding strength of the consolidated material.
[0020] In summary, the present invention has the following beneficial effects: in the process of mixing and stirring component A, component B and component C in the present application, fly ash can be effectively filled in the gaps of cement particles, so that the density of the consolidated material formed after spraying or grouting is relatively high, and as the cement hydration reaction proceeds, the active groups in the polyurethane emulsion exchange with the free calcium ions, aluminum ions and iron ions in the cement hydration to form special bridge bonds, and physical and chemical adsorption occurs around the cement particles to form a continuous phase with high uniformity, thereby reducing the overall elastic modulus, improving the physical organization structure and internal stress state of the cement slurry, and increasing the deformation resistance. In this process, lithium carbonate can absorb and release the heat of cement hydration to avoid excessively high reaction temperature, and lithium carbonate is present in the cement hydration reaction process in the consolidated material. A dense protective film is generated on the surface to prevent acidic substances and salts from corroding the internal structure of the material and improve the durability of the consolidated material. In addition, the addition of lithium carbonate can promote the coagulation of the consolidated material after spraying and shorten the coagulation time of the consolidated material. Therefore, the synergistic effect of the raw materials in components A, B and C in the present application can not only shorten the coagulation time of the consolidated material, but also improve the compressive strength and adhesion of the consolidated material, so that the initial coagulation time of the consolidated material is within 15 minutes, the final coagulation time is within 40 minutes, the compressive strength in 1 day is above 25 MPa, and the compressive strength in 3 days is above 28 MPa. Therefore, for gaps that need to be sealed or gaps with leakage, the consolidation material obtained in the present application can be sprayed or grouted to make the gaps coagulate quickly, thereby playing an effective sealing role.
[0021] In addition, the reinforcement surface formed by the consolidation material of the present application after spraying or grouting will not spontaneously combust after being ignited, and has a good flame retardant effect. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below with reference to the embodiments.
[0023] The raw materials used in the examples and comparative examples of the present application are all commercially available.
[0024] Example 1
[0025] A method for preparing a high-viscosity consolidation material for mining comprises the following steps: 35 kg of rapid hardening sulphoaluminate cement, 20 kg of coal gangue powder, 15 kg of sulphoaluminate cement, 2 kg of plastic expansion agent, 0.5 kg of polycarboxylate water reducer, 5 kg of fly ash, 5 kg of slag cement, 0.2 kg of lithium carbonate and 1 kg of retarder were mixed and stirred for 10 minutes to obtain component A; 60 kg of Portland cement, 5 kg of calcium carbonate, 10 kg of calcium oxide and 1 kg of retarder were mixed and stirred for 10 minutes to obtain component B; 70kg of polyurethane emulsion, 1kg of cellulose, 9kg of water and 0.5kg of water reducer are mixed and stirred for 10 minutes to obtain component C; component A, component B and component C are mixed in a weight ratio of 1:0.5:0.5. Specifically, 80kg of component A, 40kg of component B and 40kg of component C are mixed. When mixing, 80kg of component A and 20kg of component C are mixed and stirred for 10 minutes to obtain mixture 1, and 40kg of component B and the remaining 20kg of component C are mixed and stirred for 10 minutes to obtain mixture 2. The mixture is mixed with the mixture one and the mixture two for 10 minutes to obtain a high-viscosity consolidation material for mining; wherein the retarder in the component A and the component B consists of sodium gluconate, tartaric acid and citric acid in a weight ratio of 1:0.5:1, the fly ash adopts grade I fly ash, the plastic expansion agent has a density of 300-600g / L, an average particle size of 3.9±0.6μm, and the properties of the polyurethane emulsion are: solid content 52±1%, viscosity 500-2000mPa·s, and pH value 7-8.
[0026] Example 2
[0027] A method for preparing a high-viscosity consolidation material for mining comprises the following steps: 40 kg of rapid hardening sulphoaluminate cement, 25 kg of coal gangue powder, 17 kg of sulphoaluminate cement, 3 kg of plastic expansion agent, 1 kg of polycarboxylate water reducer, 6 kg of fly ash, 5 kg of slag cement, 0.4 kg of lithium carbonate and 1 kg of retarder were mixed and stirred for 15 minutes to obtain component A; Mix 65 kg of Portland cement, 6 kg of calcium carbonate, 12 kg of calcium oxide and 1 kg of retarder and stir for 15 minutes to obtain component B; 75kg of polyurethane emulsion, 2kg of cellulose, 15kg of water and 0.5kg of polycarboxylate water reducer were mixed and stirred for 15 minutes to obtain component C. Component A, component B and component C were mixed in a weight ratio of 1:0.5:0.5. Specifically, 80kg of component A, 40kg of component B and 40kg of component C were mixed. When mixing, 80kg of component A and 20kg of component C were mixed and stirred for 15 minutes to obtain a mixture. 40kg of component B and the remaining 20kg of component C were mixed and stirred for 5 minutes. The mixture is stirred and mixed for 15 minutes to obtain a high-viscosity consolidation material for mining; wherein the retarder in component A and component B consists of sodium gluconate, tartaric acid and citric acid in a weight ratio of 1:0.5:1, the fly ash adopts grade I fly ash, the plastic expansion agent has a density of 300-600g / L, an average particle size of 3.9±0.6μm, and the properties of the polyurethane emulsion are: solid content 52±1%, viscosity 500-2000mPa·s, and pH value 7-8.
[0028] Example 3
[0029] A method for preparing a high-viscosity consolidation material for mining comprises the following steps: 45 kg of rapid hardening sulphoaluminate cement, 30 kg of coal gangue powder, 20 kg of sulphoaluminate cement, 4 kg of plastic expansion agent, 1.5 kg of polycarboxylate water reducer, 8 kg of fly ash, 8 kg of slag cement, 0.6 kg of lithium carbonate and 3 kg of retarder were mixed and stirred for 20 minutes to obtain component A; Mix 70 kg of Portland cement, 9 kg of calcium carbonate, 15 kg of calcium oxide and 3 kg of retarder and stir for 15 minutes to obtain component B; 80kg of polyurethane emulsion, 3kg of cellulose, 17kg of water and 0.8kg of polycarboxylate water reducer are mixed and stirred for 20 minutes to obtain component C; component A, component B and component C are mixed in a weight ratio of 1:0.5:0.5. Specifically, 80kg of component A, 40kg of component B and 40kg of component C are mixed and stirred for 20 minutes to obtain a mixture 1; 40kg of component B and the remaining 20kg of component C are mixed and stirred for 20 minutes. Mixture 2 is obtained, and then mixture 1 and mixture 2 are stirred and mixed for 15 minutes to obtain a high-viscosity consolidation material for mining; wherein the retarder in component A and component B is composed of sodium gluconate, tartaric acid and citric acid in a weight ratio of 1:0.5:1, fly ash adopts grade I fly ash, the plastic expansion agent has a density of 300-600g / L, an average particle size of 3.9±0.6μm, and the properties of the polyurethane emulsion are: solid content 52±1%, viscosity 500-2000mPa·s, and pH value 7-8.
[0030] Example 4
[0031] A method for preparing a high-viscosity consolidation material for mining comprises the following steps: 45 kg of rapid hardening sulphoaluminate cement, 30 kg of coal gangue powder, 20 kg of sulphoaluminate cement, 5 kg of plastic expansion agent, 1.5 kg of polycarboxylate water reducer, 10 kg of fly ash, 8 kg of slag cement, 0.8 kg of lithium carbonate and 3 kg of retarder were mixed and stirred for 20 minutes to obtain component A; Mix 70 kg of Portland cement, 12 kg of calcium carbonate, 15 kg of calcium oxide and 3 kg of retarder and stir for 20 minutes to obtain component B; 80 kg of polyurethane emulsion, 3 kg of cellulose, 22 kg of water and 1 kg of polycarboxylate water reducer are mixed and stirred for 20 minutes to obtain component C. Component A, component B and component C are mixed in a weight ratio of 1:1:1. Specifically, 80 kg of component A, 80 kg of component B and 80 kg of component C are mixed and stirred for 20 minutes to obtain a mixture 1. 80 kg of component B and the remaining 40 kg of component C are mixed and stirred for 20 minutes to obtain a mixture 2. The mixture is mixed with the mixture one and the mixture two for 20 minutes to obtain a high-viscosity consolidation material for mining; wherein the retarder in the component A and the component B consists of sodium gluconate, tartaric acid and citric acid in a weight ratio of 1:0.5:1, the fly ash adopts grade I fly ash, the plastic expansion agent has a density of 300-600g / L, an average particle size of 3.9±0.6μm, and the properties of the polyurethane emulsion are: solid content 52±1%, viscosity 500-2000mPa·s, and pH value 7-8.
[0032] Example 5
[0033] A method for preparing a high-viscosity consolidation material for mining, which is different from Example 3 in that the raw materials in component C are 80 kg of polyurethane emulsion, 3 kg of cellulose, 22 kg of water, 1 kg of polycarboxylic acid water reducer, and 10 kg of gypsum, and the rest are the same as Example 3.
[0034] Example 6
[0035] A method for preparing a high-viscosity consolidation material for mining, which is different from Example 3 in that the raw materials in component C are 80 kg of polyurethane emulsion, 3 kg of cellulose, 22 kg of water, 1 kg of polycarboxylic acid water reducer, and 12 kg of gypsum, and the rest are the same as Example 3.
[0036] Example 7
[0037] A method for preparing a high-viscosity consolidation material for mining, which is different from Example 3 in that the raw materials in component C are 80 kg of polyurethane emulsion, 3 kg of cellulose, 22 kg of water, 1 kg of polycarboxylic acid water reducer, and 15 kg of gypsum, and the rest are the same as Example 3.
[0038] Example 8
[0039] A method for preparing a high-bonding consolidation material for mining is different from that of Example 6 in that an equal amount of UEA expansion agent is used in component A instead of a plastic expansion agent, and the rest is the same as that of Example 6.
[0040] Example 9
[0041] A method for preparing a high-viscosity consolidation material for mining, which is different from Example 6 in that the retarder consists of sodium gluconate, tartaric acid and citric acid in a weight ratio of 1:1.2:1, and the rest is the same as Example 6.
[0042] Example 10
[0043] A method for preparing a high-viscosity consolidation material for mining, which is different from Example 6 in that the expansion agent in component A is a mixture of a plastic expansion agent and a UEA expansion agent, and the weight ratio of the plastic expansion agent to the UEA expansion agent is 1:1, that is, the content of the plastic expansion agent is 2 kg, and the content of the UEA expansion agent is 2 kg, and the rest is the same as Example 6.
[0044] Embodiment 11 A method for preparing a high-bonding consolidation material for mining is different from that of Example 10 in that the fly ash in component A is grade II fly ash, and the rest is the same as that of Example 10.
[0045] Comparative Example 1 A method for preparing a high-viscosity consolidation material for mining, which is different from Example 10 in that there is no polyurethane emulsion in component C, and the rest is the same as Example 10.
[0046] Comparative Example 2 A method for preparing a high-bonding consolidation material for mining is different from that of Example 10 in that an equal amount of water-soluble epoxy resin emulsion is used in component C instead of polyurethane emulsion, and the rest is the same as that of Example 10.
[0047] Comparative Example 3 A method for preparing a high-viscosity consolidation material for mining, which is different from Example 10 in that an equal amount of vinyl acetate-ethylene copolymer emulsion is used instead of polyurethane emulsion in component C, and the rest is the same as Example 10, wherein the properties of the vinyl acetate-ethylene copolymer emulsion are: pH value 4.0-6.0, viscosity (25°C) 500-1000mPa·s, solid content ≥54.5%, ethylene content 16±2%, and the rest is the same as Example 10.
[0048] Comparative Example 4 A method for preparing a high-viscosity consolidation material for mining, which is different from Example 10 in that component A contains no lithium carbonate, and the rest is the same as Example 10.
[0049] Comparative Example 5 A method for preparing a high-viscosity consolidation material for mining, which is different from Example 10 in that an equal amount of sodium carbonate accelerator is used in component A instead of lithium carbonate, and the rest is the same as Example 10.
[0050] Performance Testing The setting time, compressive strength, flexural strength and bonding strength of the high-bonding materials for mining obtained in the above-mentioned embodiments, comparative embodiments and comparative examples were tested. The test results are shown in Table 1.
[0051] The compressive strength, flexural strength and setting time are tested according to the relevant provisions of GB / T50448-2015 "Technical Specifications for Application of Cement-based Grouting Materials"; The bonding strength is tested in accordance with the relevant provisions of JT / T1211.1-2018 "Rapid Repair Materials for Cement Concrete in Highway Engineering".
[0052] Table 1 Test results of high bonding material properties
[0053] From Table 1 we can see that: The high-bonding consolidation material obtained in the embodiment of the present application has an initial setting time of within 15 minutes, a final setting time of within 40 minutes, and has good bonding strength, compressive strength and flexural strength, indicating that the strength of the consolidation material can be effectively improved after the raw materials of component A, component B and component C in the present application are mixed.
[0054] Compared with Example 3, after gypsum is added to component C, the compressive strength, flexural strength and bonding strength of the consolidated material in Examples 5-7 are all improved compared with the compressive strength, flexural strength and bonding strength in Example 3. The reason is that during the cement hardening process, gypsum can act as a catalyst to promote chemical reactions in the cement hydration reaction process. These reactions can promote faster growth of cement crystals, which can further improve the strength of the consolidated material.
[0055] Compared with Example 6, when the expansion agent is a combination of a plastic expansion agent and a UEA expansion agent, the setting time of the consolidated material obtained in Example 10 is lower than the setting time of the consolidated material in Example 6, and the compressive strength, flexural strength and bonding strength of the consolidated material obtained in Example 10 are better than the compressive strength, flexural strength and bonding strength of the consolidated material obtained in Example 6. The reason may be that the plastic expansion agent can improve the pores and porosity inside the consolidated material through diffusion, making the interior of the consolidated material more uniform, thereby improving the compactness of the consolidated material. The UEA expansion agent reacts with water during the cement hydration reaction to generate an expanded crystalline hydrate, calcium aluminate, so that the consolidated material expands moderately in the early stage. Under the constraint of cellulose, its expansion is converted into stress pressure, which can offset the stress generated when the consolidated material shrinks, reduce the cracking of the consolidated material, and make the consolidated material dense.
[0056] Compared with Example 10, when the C component raw material lacks polyurethane emulsion, the solidification time of the solidified material obtained in Comparative Example 1 is long, and the compressive strength, flexural strength and bonding strength are much lower than the compressive strength, flexural strength and bonding strength of the solidified material obtained in Example 10, indicating that the addition of polyurethane emulsion can effectively improve the compressive strength, flexural strength and bonding strength of the solidified material, and can also shorten the solidification time of the solidified material.
[0057] Compared with Example 10, when the water-soluble epoxy resin emulsion and the vinyl acetate-ethylene copolymer emulsion are used to replace the polyurethane emulsion respectively, the compressive strength, flexural strength and bonding strength of the consolidated material obtained in Comparative Example 2-3 are much lower than the compressive strength, flexural strength and bonding strength of the consolidated material obtained in Example 10, and the setting time of the consolidated material obtained in Comparative Example 2-3 is also relatively long. This can further illustrate that the combination of polyurethane emulsion with cement, cellulose and other raw materials can effectively ensure the strength of the consolidated material.
[0058] Compared with Example 10, when lithium carbonate is missing in component A or sodium carbonate accelerator is used instead of lithium carbonate, the solidification material obtained in Comparative Example 4-5 has a long setting time, and the compressive strength, flexural strength and bonding strength are all lower than those in Example 10. It can be seen that lithium carbonate not only plays a role in accelerating setting in the present application, but also can react with cement to achieve the effect of improving the strength of the solidification material.
[0059] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-viscosity consolidation material for mining, characterized in that: The invention is composed of component A, component B and component C in a weight ratio of 1: (0.5-1): (0.5-1), wherein component A comprises the following raw materials in parts by weight: 35-45 parts of rapid hardening sulphoaluminate cement, 20-30 parts of coal gangue powder, 15-20 parts of sulphoaluminate cement, 2-5 parts of expansion agent, 0.5-1.5 parts of water reducing agent, 5-10 parts of fly ash, 5-8 parts of slag cement, 0.2-0.8 parts of lithium carbonate and 1-3 parts of retarder; The B component includes the following raw materials in parts by weight: 60-70 parts of Portland cement, 5-12 parts of calcium carbonate, 10-15 parts of calcium oxide, and 1-3 parts of retarder; The C component comprises the following raw materials in parts by weight: 70-80 parts of polyurethane emulsion, 1-3 parts of cellulose, 9-22 parts of water, and 0.5-1 part of water reducing agent.
2. The high-bonding consolidation material for mining according to claim 1, characterized in that: The component A comprises the following raw materials in parts by weight: 40-45 parts of rapid hardening sulphoaluminate cement, 25-30 parts of coal gangue powder, 17-20 parts of sulphoaluminate cement, 3-4 parts of expansion agent, 1.0-1.5 parts of water reducing agent, 5-10 parts of fly ash, 5-8 parts of slag cement, 0.2-0.8 parts of lithium carbonate, and 1-3 parts of retarder; The B component includes the following raw materials in parts by weight: 65-70 parts of Portland cement, 6-9 parts of calcium carbonate, 12-15 parts of calcium oxide, and 1-3 parts of retarder; The C component comprises the following raw materials in parts by weight: 75-80 parts of polyurethane emulsion, 2-3 parts of cellulose, 9-22 parts of water, and 0.5-1 part of water reducing agent.
3. A high-bonding consolidation material for mining according to claim 1 or 2, characterized in that: The C component also includes 10-15 parts by weight of gypsum.
4. A high-bonding consolidation material for mining according to claim 1 or 2, characterized in that: The fly ash is Grade I fly ash.
5. A high-bonding consolidation material for mining according to claim 1 or 2, characterized in that: The expansion agent is a plastic expansion agent, a UEA expansion agent, or a combination of the two.
6. The high-bonding consolidation material for mining according to claim 5, characterized in that: The weight ratio of the plastic expansion agent to the UEA expansion agent is 1:
1.
7. A high-bonding consolidation material for mining according to claim 1 or 2, characterized in that: The retarder is composed of sodium gluconate, tartaric acid and citric acid in a weight ratio of 1: (0.5-1.2):
1.
8. The high-bonding consolidation material for mining according to claim 1, characterized in that: The solid content of the polyurethane emulsion is 40-50%.
9. A method for preparing a high-bonding consolidation material for mining according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing and stirring various raw materials in component A for 10-20 minutes to obtain component A; mixing and stirring various raw materials in component B for 10-20 minutes to obtain component B, mixing and stirring various raw materials in component C for 10-20 minutes to obtain component C, stirring and mixing component A and half of component C for 10-20 minutes to obtain mixture one, stirring and mixing component B and the remaining half of component C for 10-20 minutes to obtain mixture two, and stirring and mixing mixture one and mixture two for 10-20 minutes to obtain a high-viscosity consolidation material for mining.
Citation Information
Patent Citations
Tunnel grouting material applicable to use in low-temperature environment
CN105174877A
Double-doped grouting material for repairing pavement and preparation method of double-doped grouting material
CN107840626A
Compound of quick-setting rapid-hardening cement material and preparation method thereof
CN108069649A
Polymer quick-hardening cement mortar and method for quick repair of waterproof coil concrete protecting layer
CN109231935A
Overspeed mining inorganic reinforcing material and preparation method thereof
CN110818371A
Cited By
Coal gangue micro-expansion sealing material as well as preparation method and application thereof
CN121449388A